IDEOLOGY, TECHNOLOGY AND TRANSLATION IMPACT (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This study investigates the intricate relationship between ideology, technology, and translation, examining how these factors shape and influence translation processes and outcomes in contemporary contexts. The research analyzes the ways in which ideological frameworks affect translators' choices and strategies, while simultaneously exploring how technological advancements have transformed translation practices and accessibility. Аннотация: В данном исследовании рассматривается сложная взаимосвязь между идеологией, технологией и переводом, анализируется как эти факторы формируют и влияют на процессы и результаты перевода в современных контекстах. В исследовании анализируются способы, которыми идеологические рамки влияют на выбор и стратегии переводчиков, одновременно исследуя, как технологические достижения трансформировали практику перевода и его доступность.